Задача механики разрушения для биматериала с дискообразной межслоевой трещиной под воздействием волны сдвига - Меньшиков, В.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The paper is devoted to the solution of a fracture mechanics problem for a penny-shaped open crack located at the interface between dissimilar materials under a normally incident shear wave. Stress intensity factors (opening mode, transversal and longitudinal shear modes) are computed, by using the stress and displacement fields obtained in the vicinity of crack’s front.